Harnessing forests for climate change mitigation through REDD+: challenges and opportunities - Kanninen, M.; Brockhaus, Maria; Murdiyarso, Daniel; Nabuurs, G.J. (IUFRO, 2010)
Deforestation, forest degradation, and land-use change are a major source of carbon emissions. The Copenhagen Accord recognised the crucial role of reducing emissions from deforestation, emphasized the role of forests in climate change mitigation, and called for the immediate establishment of a REDD+ mechanism. Most likely, it will form an integral part of the future climate change regime. For many developed countries, REDD+ seems to be an attractive option to achieve part of their reduction targets through investments in developing countries. For some developing countries, this offers an additional source of financing to support sustainable forest management and to boost their development plans and poverty-reduction strategies. This paper analyses the challenges and major gaps that developing countries are facing when planning their national strategies for the implementation of REDD+ schemes. We conclude that REDD+ as a climate change mitigation instrument will only be able to proceed at a pace that allows the meaningful participation of all relevant stakeholders in consensus-building. When the REDD+ enters the markets, the rights of local communities to forest land and carbon will need to be clarified and secured. Successful implementation of REDD+ will, in most cases, require strengthening the stake of local communities for managing their forest carbon assets and allowing them to benefit fully from emerging carbon markets and other funding schemes. Governments will need to renew their institutions and adopt new approaches to handle these challenges by including the role of forests in climate change mitigation as an integral part of their development plans and policies.